Effect of Low‐Income Unmarried Fathers' Presence at Birth on Involvement. Issue 3 (16th March 2015) - Bellamy, Jennifer L.; Thullen, Matthew; Hans, Sydney
Abstract The birth of a child represents a unique window of opportunity to understand and support ongoing father involvement among low‐income unmarried parents. Using data collected as part of a randomized controlled trial of a community‐based home visiting intervention provided to 248 low‐income African American women, a propensity score matching approach was used to estimate the effect of fathers' presence at birth on multiple measures of later father involvement over the first 2 years postpartum. The results indicated that participation in child care activities is the only form of involvement predicted by presence at birth at 4 months, and none of the forms of father involvement measured were predicted at 12 months; however, presence at birth was predictive of all 7 indicators of involvement at 24 months. Engaging fathers in the birth experience may represent an important opportunity to provide services.